2018
DOI: 10.1016/j.jns.2018.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Motor and non-motor features of Parkinson's disease in LRRK2 G2019S carriers versus matched controls

Abstract: Prevalence of the LRRK2 G2019S mutation in AJ and non-AJ subjects in our study population in Cleveland, Ohio was comparable to other clinical studies. There were no significant motor or non-motor differences between LRRK2+ PD and matched PD controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The studies identified in this review confirm prior findings of especially high prevalence of the G2019S variant among patients with PD who are Ashkenazi Jewish (14.8%, based on estimates from the United States [5,[27][28][29] and Israel [30,31]) and Berber Arab (35.9%, based on estimates from two studies [7,18] spanning Morocco, Tunisia, Algeria, Libya, and France).…”
Section: G2019ssupporting
confidence: 82%
“…The studies identified in this review confirm prior findings of especially high prevalence of the G2019S variant among patients with PD who are Ashkenazi Jewish (14.8%, based on estimates from the United States [5,[27][28][29] and Israel [30,31]) and Berber Arab (35.9%, based on estimates from two studies [7,18] spanning Morocco, Tunisia, Algeria, Libya, and France).…”
Section: G2019ssupporting
confidence: 82%
“…The response to levodopa therapy was similar within these two groups: 88% of LRRK2 mutated patients showed a positive response, compared with 83% of IPD patients [16]. Concerning the other symptoms, such as depression, hyposmia, urinary urgency or incontinence, motor fluctuations and dyskinesia, no difference was observed between these two groups [17][18][19][20][21]. Lastly, no atypical signs have been reported in patients with LRRK2 mutations [22].…”
Section: Lrrk2 (Park8)mentioning
confidence: 72%
“…Some reports indicate greater cognitive deficits and/or progression in familial forms such as SNCA and GBA, 73,74 whereas others show the opposite [75][76][77] or no clinical differences. 78,79 Future studies are needed to better delineate any clinical differences between IPD and FPD.…”
Section: Discussionmentioning
confidence: 99%